FAKTOR-FAKTOR YANG MEMPENGARUHI AGRESIVITAS SISWA KELAS VII SMPN 8 PEKANBARU - Dicky Setiady; Tri Umari; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to understand the internal factors affecting aggressiveness, description of external factors affecting aggressiveness, per-item description of internal factors affecting aggressiveness, and per-item description of external factors affecting aggressiveness. Method in this research is descriptive quantitative method with sample of student of class VII as many as 200 people from population as much as 384. The research conducted in September. Data and research instruments were obtained through questionnaires that were processed using statistical formula. Based on the recapitulation of the scores that have been processed, the results obtained: internal factors affecting student aggressiveness seen almost half are in very low category of 49%, sedamgkan external factors that affect student aggressiveness seen more than half are in very low category that is 58 %. Internal factor which more dominant influence student aggressiveness is on indicator